Discovery of novel leucyladenylate sulfamate surrogates as leucyl-tRNA synthetase (LRS)-targeted mammalian target of rapamycin complex 1 (mTORC1) inhibitors. Issue 14 (7th August 2018) - Yoon, Suyoung; Zuo, Dongxu; Kim, Jong Hyun; Yoon, Ina; Ann, Jihyae; Kim, Sung-Eun; Cho, Dasol; Kim, Won Kyung; Lee, Sangkook; Lee, Jiyoun; Kim, Sunghoon; Lee, Jeewoo
Graphical abstract: Abstract: According to recent studies, leucyl-tRNA synthetase (LRS) acts as a leucine sensor and modulates the activation of the mammalian target of rapamycin complex 1 (mTORC1) activation. Because overactive mTORC1 is associated with several diseases, including colon cancer, LRS-targeted mTORC1 inhibitors represent a potential option for anti-cancer therapy. In this work, we developed a series of simplified leucyladenylate sulfamate analogues that contain the N -(3-chloro-4-fluorophenyl)quinazolin-4-amine moiety to replace the adenine group. We identified several compounds with comparable activity to previously reported inhibitors and exhibited selective mTORC1 inhibition and anti-cancer activity. This study further supports the hypothesis that LRS is a promising target to modulate the mTORC1 pathway.